The Role Of Technology In Developing ESP Learning Materials - Muhlisin, Muhammad; Imran, Fathurrahman (JUPE : Jurnal Pendidikan Mandala, 2025)
This study explores how social media contributes to second language acquisition (SLA), focusing on sixth-semester English education students at FBMB UNDIKMA. Using a mixed-methods approach, the research gathered data through surveys and interviews to understand how students interact with English-language content on platforms like YouTube, Instagram, and TikTok. The quantitative results showed a clear connection between how often students used social media and how much they felt their vocabulary and grammar had improved. Meanwhile, the qualitative findings painted a richer picture: students often picked up new vocabulary by accident, became more attuned to grammar use, and felt more motivated to engage with the language. These findings are consistent with well-established SLA theories, such as Krashen’s Input Hypothesis and Schmidt’s Noticing Hypothesis, which emphasize the value of exposure and awareness in language learning. Overall, the study suggests that social media, while informal, can effectively complement classroom learning—especially when teachers recognize and incorporate students’ existing digital habits into their teaching practices.